Inventory Cost Reduction and EOQ for Personal Protective Equipment: A Case Study in Oil and Gas Company - Andian Ari Istiningrum; Sono Sono; Virgy Andika Putri (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
Personal Protective Equipment (PPE) is one of materials that is urgent for oil and gas companies. Company X is an upstream oil and gas company located in Indonesia that requires its employees to wear PPE. Therefore, the PPE inventory must be controlled carefully to maintain the level of PPE inventory. This research has an objective to reduce PPE inventory cost through the application of Economic Order Quantity (EOQ) method. To achieve this objectives, a research was conducted to 22 items of PPE in Company X. The research was conducted by forecasting PPE demand, calculating optimal quantity and ordering frequency, calculating safety stock and reorder point, and finally calculating the inventory cost reduction. The result shows that the implementation of EOQ has enabled the company to reduce its inventory cost by 19.72%. Therefore, it is advisable for Company X to design and implement EOQ as the inventory control program for PPE.